Analisa Sea Level Rise Dari Data Satelit Altimetri Topex/Poseidon, Jason-1 Dan Jason-2 Di Perairan Laut Pulau Jawa Periode 2000 – 2010 - Hastho Wuriatmo; Sorja Koesuma; Mohtar Yunianto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
It has been conducted a research about sea level rise (SLR) in surrounding Jawa island by using satellite altimetry data Topex/Poseidon, Jason-1 dan Jason-2 for period 2000 – 2010. Satellite altimetry is satellite which specially design for measuring dynamics of sea water. Those satellite lauched firstly in 1992 incorporation between National Aeronautics and Space Administration (NASA) dan European Space Agency (ESA). There are six locations for measuring SLR i.e. Jakarta, Semarang, Surabaya, Pangandaran, Jogjakarta dan Prigi. We choselocations based on alongtrack of satellite and near the big cities in Jawa island with dimension area around 0.5ox0.5o degrees. We found SLR rate for Jakarta (2.5 ± 0.24 mm/yr), Semarang (2.16 ± 0.20 mm/yr), Surabaya (2.72 ± 0.19 mm/yr), Pangandaran (0.71 ± 0.33 mm/yr), Jogjakarta (0.91 ± 0.38 mm/yr) and Prigi (1.3 ± 0.38 mm/yr). The average SLR rate for North coast is (2.46 ± 0.21 mm/yr) and for South coast (0.97 ± 0.36 mm/yr). This results are wellcorrelated with data from tide gauge stations.